Pengaruh Pengetahuan Kewirausahaan, E-Commerce Dan Penggunaan Sistem Informasi Akuntansi, Terhadap Pengambilan Keputusan Berwirausaha - Selvia, Selvia; Nusantoro, Jawoto; Darmayanti, E Febri (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to analyze Entrepreneurship Knowledge, E-commerce, and Use of Accounting Information Systems on Entrepreneurial Decisions in Students of the Accounting Study Program, Faculty of Economics and Business, University of Muhammadiyah Metro. The population in this research is 268 respondents. The sampling technique in this research used several respondent criteria to obtain a sample of 86 respondents. The data in this study used SPSS version 22 with multiple linear regression analysis testing. The results of this study indicate that entrepreneurial knowledge, e-commerce, and the use of accounting information systems have a partial or simultaneous effect on Entrepreneurial Decisions in Students of the Accounting Study Program, Faculty of Economics and Business, University of Muhammadiyah Metro